PENERAPAN KEBIJAKAN HUKUM ATAS PERJANJIAN ASEAN CHINA FREE TRADE AREA (ACFTA) TERHADAP PEMBEBASAN BEA MASUK SEKTOR INDUSTRI TEKSTIL USAHA MIKRO KECIL DAN MENENGAH - Erni, Wina (Jurnal De Lege Ferenda Trisakti, 2025)
The aim of this research is to determine the impact of implementing the ASEAN China Free Trade Area Agreement as a result of the elimination of trade barriers, both tariffs and non-tariffs, in the textile and textile product industry sector. The method used in this research is an empirical normative method with a constitutional approach. The implementation of the ASEAN China Free Trade Area Agreement (ACFTA) does not always go according to its initial objectives. After the implementation of Free Trade through the ASEAN China Free Trade Area (ACFTA), problems arose resulting from the implementation of the ASEAN China Free Trade Area, giving rise to economic inequality, especially in the textile industry for Small and Medium Enterprises (MSMEs). The results of this research are that the existence of legal regulations governing Free Trade, especially Import Duties, causes domestic textile production costs to increase while domestic textile sales decrease. Apart from that, another causal factor is the inability to compete with other countries due to free trade barriers. In this case, regulations regarding textile raw materials must be updated so that Indonesia can produce its own textile raw materials without having to import from other countries. Therefore, the implementation of the ASEAN China Free Trade Area (ACFTA) must be followed by appropriate legal policies to provide protection for textile entrepreneurs in Indonesia